Physical Activity Profile of Older Elementary School Children of Batac, Ilocos Norte using the Modified Physical Activity Questionnaire for Older Children - Aurelio, Manuel Ted F. (JPAIR Multidisciplinary Research, 2008)
Physical activity has been consistently shown to have strong positive correlations with both physical and mental health benefits for adults and children alike, supporting the importance of early intervention programs to promote lifelong healthy habits. However, despite these benefits, there is a notable lack of local studies examining the physical activity levels of Filipino children, contrasting with the extensive foreign literature available. To address this gap, a study was conducted in Batac, Ilocos Norte, using the Modified Physical Activity Questionnaire for Children (MPAQ-C) among 238 elementary school students aged 8 to 12 years. The results showed that "tagging" was the most common activity (7.509%), while "karate" was the least (3.325%). Children were most active during weekends but showed restricted activity on school days, with mild activity in PE classes often limited to classroom work. Outside school, they engaged in sports, dance, or play. Mean physical activity peaked at age 10 and declined by age 12, though ANOVA revealed no significant differences across age groups (f value = 1.135, a = 0.05). Height was the only variable significantly affecting physical activity levels (r = 0.173), indicating taller children may be more inclined to engage in physical activities. Overall, the study highlights the need for targeted interventions to enhance physical activity among Filipino children, reinforcing its importance in their development and suggesting that educators and policymakers can develop more effective strategies by understanding these patterns and factors.
Keywords: Physical Activity; Children; Modified Physical Activity Questionnaire; Health